Bio-hydrogen Production from Rabbit Dung by Anaerobic Self-fermentation - Sucheera Laocharoen (Science Faculty of Chiang Mai University, 2019)
Bio-hydrogen production from rabbit dung was investigated in this study. Rabbit dung was subjected to four different pre-treatment methods prior to hydrogen fermentation including acid (adjusted to pH 3, maintained for 24 h); base (adjusted to pH 10, maintained for 24 h); aeration (flushed with air for 24 h); and chloroform (0.1 % chloroform, 24 h). The fermentation was conducted using 50 g-total solid (TS)/L, an initial pH of 6, and an incubation temperature of 37 °C at 150 rpm without inoculation. Results indicated that the pre-treatment methods did not improve hydrogen production efficiency from rabbit dung. Therefore, the untreated rabbit dung was used as the substrate for hydrogen production without seed inoculum. The optimum conditions for achieving maximum hydrogen production from untreated rabbit dung were further investigated and the results showed that a TS concentration of 150 g-TS/L, initial pH of 5.5 and temperature of 30 °C gave a maximum hydrogen yield, hydrogen production, and hydrogen rate of 25 ml-H2/g-TS added, 3810 ml/H2/L and 36 ml-H2/h, respectively.